USING E-BOOKS TO IMPROVE ENGLISH READING COMPREHENSION OF SECONDARY SCHOOL STUDENTS - Rahmatillah Rahmatillah; Syarifuddin Dollah; Munir Munir (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2026)
This study, conducted on 30 eighth grade students at SMP Negeri 27 Makassar using a pre-experimental one-group pretest-posttest design, aimed to evaluate the effectiveness of e-books in improving English reading comprehension and gauge student interest in the digital medium. The results showed that e-books were highly effective. Students' reading comprehension scores saw a statistically significant increase (significance value of 0.000), rising sharply from a "Very Poor" average of 47.67 to a "Good" average of 85.67. This 38-point gain resulted in a high N-Gain score of 0.72. Furthermore, the interest questionnaire revealed that students were highly engaged, with the majority reporting moderate to high interest in using e-books. Overall, the findings confirm that e-books are an effective teaching tool that successfully improves reading skills while simultaneously boosting student interest in English language learning.Keywords: e-book, reading comprehension, student interest, digital learning, English Stories app